CYBERPUNK – GAME – POETRY: Rostislav Amelin’s “SimStab” - Daniil Leiderman; Mark Lipovetsky (Internationale Zeitschrift für Kulturkomparatistik)
The article discusses “SimStab” [Simulator of Stability], a poetic performance by a young Russian poet, Rostislav Amelin, as an effective hybrid of the innovative poetry, video game, and the cyberpunk genre models. The interaction of these components produces strong, yet not necessarily obvious political over-tones, testing the limits of the audience’s (or readers’, or players’) agency. Like many other cyberpunk texts, “SimStab” explores the conflict between the desire to resist colonization by the pervasive powers dominating contemporary society, and the absolute necessity of willingly colonizing your own body and subjectivity with the products of these powers. Both the poem, game and their shared text embody spaces of utopia reliant on repressed sites of formless abjection, which paradoxically become a source of anarchic freedom. Thus, in “SimStab” the ludic algorithmic with its procedural rhetoric (Ian Bogost) creates spaces of formlessness which repeats the liberatory promise of cyberpunk literature.